The Effectiveness of Problem-Solving Strategy in Enhancing the Achievement of Fourth Grade Preparatory Students in Mathematics - عطا الله, فاضل عبد العباس (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The aim of the research is to understand the importance of problem-solving in increasing academic achievement in mathematics. The researcher conducted the experiment on secondary school students، who were the targeted and primary sample. In the same context، the test was administered specifically to fourth-grade students in both the scientific and literary branches، totaling 148 male and female students. A test was prepared to determine the relationship between problem-solving and academic achievement in mathematics. The final test consisted of 25 items after being reviewed by experts and specialists in the fields of education and teaching. The number of students who participated in this test was 74 male students and 74 female students. The results of the test and data analysis showed that problem-solving has significant importance in teaching mathematics. The relationship between problem-solving and academic achievement is a positive linear relationship، meaning that as students acquire better problem-solving skills، their academic achievement in mathematics increases.